Refinement of Wingless expression by a Wingless- and Notch-responsive homeodomain protein, defective proventriculus. - Nakagoshi, H.; Shirai, T.; Nabeshima, Y.I.; Matsuzaki, F. (Developmental Biology, 2002)
Pattern formation during animal development is often induced by extracellular signaling molecules, known as morphogens, which are secreted from localized sources. During wing development in Drosophila, Wingless (Wg) is activated by Notch signaling along the dorsal-ventral boundary of the wing imaginal disc and acts as a morphogen to organize gene expression and cell growth. Expression of wg is restricted to a narrow stripe by Wg itself, repressing its own expression in adjacent cells. This refinement of wg expression is essential for specification of the wing margin. Here, we show that a homeodomain protein, Defective proventriculus (Dve), mediates the refinement of wg expression in both the wing disc and embryonic proventriculus, where dve expression requires Wg signaling. Our results provide evidence for a feedback mechanism that establishes the wg-expressing domain through the action of a Wg-induced gene product.